Endosonography and magnetic resonance cholangiopancreatography show similar efficacy in selecting patients for ERCP in mild-moderate acute biliary pancreatitis - Emrah Alper; Sinan Akay; Zafer BUYRAÇ; Fatih Aslan; Işık ALPER; Belkıs Ünsal (Turkish Journal of Gastroenterology, 2019)
-